Post-craniotomy intracranial pressure monitoring: a novel approach combining optic nerve sheath diameter ultrasonography and cervical-cerebral arterial ultrasound - Fu, Zunfeng; Peng, Lin; Guo, Laicai; Hu, Naixia; Zhu, Yamin; Tang, Shouxin; Lou, Hongliang; Zhang, Jiajun; Wang, Chongqiang (Frontiers in Neurology, 2025)
ObjectiveElevated intracranial pressure (ICP), a common complication in traumatic brain injuries (TBI), can lead to optic nerve sheath diameter (ONSD) enlargement and flow spectrum changes from the internal carotid artery (ICA) to middle cerebral artery (MCA). This study will investigate the use of Cervical-Cerebral Arterial Ultrasound (CCAU) for non-invasive ICP assessment and evaluating the related indices’ clinical utility in TBI patients with decompressive craniotomy (DC).MethodsONSD and flow spectrum changes were measured within 24 h after DC in 106 patients via ultrasonic ONSD measurement and CCAU, simultaneously. Intracranial pressures were invasively monitored, using a microsensor or ventricular catheter as the gold standard. Patients were classified into two groups, namely the normal group and the elevated group, based on distinct intracranial pressure thresholds of 15 mmHg, 20 mmHg and 22 mmHg. Subsequently, Bland Altman plot used for evaluating agreement between estimate for ICP (ICPe) and invasive ICP (ICPi). Then, the correlation between ONSD, MCAPI (pulsatility index of MCA), PI-ratio (MCAPI/ICAPI), and ICPe was examined through linear regression analysis. Finally, receiver operator characteristic curves (ROC) were also analyzed for different indexes and their combinations (using logistic model).ResultsSignificant differences were observed between the normal and elevated ICP groups with respect to ONSD, PI-ratio, MCAPI and MCAFVd (diastolic flow velocity of MCA) (p < 0.05). The correlation coefficients for the relationships between ONSD, PI ratio, FVdMCA, and PI with ICPi were 0.62, 0.33, 0.32 and 0.21, respectively, each demonstrating statistical significance (p < 0.05). Analysis of the ROC curves demonstrated that the area under the curve (AUC) for predicting elevated ICPi at thresholds of 15 mmHg, 20 mmHg, and 22 mmHg via combined ultrasonographic measurements of the PI ratio and ONSD was the largest, specifically 0.74 (95% CI: 0.65–0.82), 0.77 (95% CI: 0.69–0.85), and 0.79 (95% CI: 0.70–0.86), respectively.ConclusionUltrasonographic measurements of ONSD, PI-ratio, MCAPI and MCAFVd demonstrate a moderate to low weak correlation with ICPi measurements. ICPe is not considered sufficiently precise for noninvasive accurate ICP assessment. The concurrent utilization of CCAU and ONSD measurements may offer superior accuracy for elevated ICP in TBI patients with DC, especially in specificity. Further research is imperative to validate these findings within a more extensive patient population.